The double-edged sword effect of ethical leadership on constructive deviance: An integrated model of two approaches based on organizational identification and normative conflict - Niu, Lixia; Xia, Wende; Liu, Yong (Frontiers in Psychology, 2022)
Based on the normative conflict model, this study proposes a dual-pathway model that is constituted of organizational identification and normative conflict, and examines the double-edged sword effect of ethical leadership on subordinates’ constructive deviance. According the analysis of 449 questionnaires collected from Chinese employees, the results show that: ethical leadership can promote employees’ constructive deviance by improving their constructive intention (Organizational identification), and it can weaken employees’ deviance motivation (normative conflict) to prevent their constructive deviance. Moreover, ethical leadership has different effects on different types of constructive deviance. This research further enriches the formation mechanism of constructive deviance and provides practical guidance to exert the effectiveness of constructive deviance in organizational management.